Textures Of Place : Exploring Humanist Geographies - Till, Karen E.; Hoelscher, Steven D.; Adams, Paul C. (Book collections on Project MUSE., 2001)
The contributors to this volume--distinguished scholars from geography, art history, philosophy, anthropology, and American and English literature--investigate the ways in which place is embedded in everyday experience, its crucial role in the formation of group and individual identity, and its ability to reflect and reinforce power relations.